1998
DOI: 10.1557/jmr.1998.0474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering additive composition on the thermal conductivity of silicon nitride

Abstract: The thermal conductivity of silicon nitride prepared with varying sintering additive compositions was studied. Samples of Si3N4 + 0.5 mol% Y2O3 + 0.5 mol% Nd2O3 and a further additional agent were gas pressure sintered at 2173 K. MgO or Al2O3 was employed as the additional agent. While both agents improved sinterability, the former promoted grain growth and the latter suppressed it. Thermal conductivity increased with increasing MgO content, and a maximum value of 128 Wm-1 K-1 was attained when 2 mol% MgO was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
3
28
1
2
Order By: Relevance
“…With the further addition of MgSiN2, the density shows an increase. This similar phenomenon was also observed by Okamoto et al 7) In their work, a β-Si3N4 powder was used as the raw material and a mixture of 0.5 mol% Y2O3 and 0.5 mol% Nd2O3 was used as the basic additive composition. They showed that the addition of 1 mol% of MgO initially inhibited the densification, but the further addition promoted the densification.…”
Section: Jcs-japansupporting
confidence: 82%
See 1 more Smart Citation
“…With the further addition of MgSiN2, the density shows an increase. This similar phenomenon was also observed by Okamoto et al 7) In their work, a β-Si3N4 powder was used as the raw material and a mixture of 0.5 mol% Y2O3 and 0.5 mol% Nd2O3 was used as the basic additive composition. They showed that the addition of 1 mol% of MgO initially inhibited the densification, but the further addition promoted the densification.…”
Section: Jcs-japansupporting
confidence: 82%
“…Okamoto et al 7) reported that the addition of 1 mol% of MgO inhibits the densification, but the further addition leads to the promoted densification, pronounced grain growth and enhanced thermal conductivity of Si3N4 ceramics using a mixture of 0.5 mol% Y2O3 and 0.5 mol% Nd2O3 as the basic additive composition. Lin et al 16) also reported that the addition of MgO has an effect on the thermal conductivity of Si3N4 ceramics with Y2O3, but its effect depends on the sintering temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Attainment of high thermal conductivity requires the use of high purity starting powders with low oxygen content and low cationic impurities, full densification of the sintered body, and the optimisation of many factors including sintering parameters [91] and sintering aid(s). Very high thermal conductivity Si 3 N 4 has been reported in many studies [94,191,[198][199][200], produced by careful control of purity and oxygen content of raw powders [94,201], selection of additives [202], control of microstructure morphology and grain size [109,178,194,197,203,204], and use of β -Si 3 N 4 seed crystals [205]. However, despite the large volume of studies reporting techniques for production of high thermal conductivity silicon nitride, typical commercially available silicon nitride [206] at present has a far lower thermal conductivity.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…However, little attention was paid to the thermal conductivity of Si 3 at room temperature [1]. A considerable amount of work resulted in significantly increased thermal conductivities of Si 3 N 4 ceramics of above 100 W m −1 K −1 [2][3][4][5][6][7]. Enhanced thermal conductivity opens up new technological applications of Si 3 N 4 as substrates for integrated circuits and heat sinks in electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The key issues in enhancing the thermal conductivity of β-Si 3 N 4 ceramics are the complete densification, purification of β-Si 3 N 4 grains and a reduced amount of grain boundary phases; all of which are dependent on the sintering additives and sintering techniques [2,7]. Dissolved O and Al in the β-Si 3 N 4 lattice are the two main impurities that lower the thermal conductivity of β-Si 3 N 4 via phonon-defect scattering, and thus the use of SiO 2 and Al 2 O 3 additives should be avoided [4,11]. To enhance the thermal conductivity, sintering additives should play a dual role of promoting densification and removing lattice oxygen.…”
Section: Introductionmentioning
confidence: 99%